An Anisotropic Nonconforming Finite Element Method for Approximating a Class of Nonlinear Sobolev Equations (Journal of Computational Mathematics, 2018)
An anisotropic nonconforming finite element method is presented for a class of nonlinear Sobolev equations. The optimal error estimates and supercloseness are obtained for both semi-discrete and fully-discrete approximate schemes, which are the same as the traditional finite element methods. In addition, the global superconvergence is derived through the postprocessing technique. Numerical experiments are included to illustrate the feasibility of the proposed method.
Keywords: Nonlinear Sobolev equations; Anisotropic; Nonconforming finite element; Supercloseness; Global superconvergence.